Gc-ms analysis of leaf and rhizome essential oil of zingiber purpureum roxb. From bangladesh (Bangladesh Journal of Botany, 2024)
Essential oils (EOs) are among the most important plant secondary metabolites. Zingiber purpureum Roxb. is a tropical ginger from Bangladesh, but its chemical constituents of leaves and rhizomes, both EOs, may have pharmacological effects. The aim of this study was carried out to analyze the qualitative composition of both Essential oils (EOs) of both leaf and rhizomes of Z. purpureum. The EOs from the leaves and rhizomes were extracted by hydrodistillation. Chemical constituents of the EOs were separated and identified by gas chromatography/mass spectrometry (GC/MS), and the relative percentage of each constituent was determined by area normalization. In total, 81 compounds were identified from leaf EOs, whereas 44 were from rhizome EOs. The common compounds identified from both rhizome and leaf EOs were triquinacene, 1,4, bis (methoxy), b-phellandrene and b-sesquiphellandrene, respectively. Besides, the major constituents of leaf EOs were sabinine (14.99%), b-pinene (14.32%), caryophyllene oxide (13.85%), and caryophyllene (9.47%), whereas the rhizome EOs confirmed (Z)-ocimene (21.97%), 4-terpineol (18.45%), γ-terpinene (3.86%) and cis-sabinenehydrate (3%). These EOs could be a promising source for the development of nutraceuticals, functional foods, and pharmaceutical products due to their potent activities and exploitation.Bangladesh J. Bot. 53(1): 153-158, 2024 (March)